Peremajaan Wisata Budaya Melalui Wisata Gastronomi Kreatif di Ubud, Bali - Ni Made Prasiwi Bestari; Agung Suryawan Wiranatha; I Gusti Ayu Oka Suryawardani; I Nyoman Darma Putra (Institut Seni Indonesia Denpasar, 2022)
The Ubud area has long been developed and is known as a cultural tourism destination. This is not surprising because Ubud has many artistic and cultural attractions to offer for tourists. However, in the last two decades, Ubud is also known as a culinary tourism destination. In fact, the Gianyar Regency government and the Ministry of Tourism and Creative Economy have promoted Ubud as gastronomic tourism. This article analyzes the role of gastronomic tourism in supporting cultural tourism in Ubud. Does the new Ubud label as gastronomic tourism fade the image of Ubud as cultural tourism or does it increase its charm and attractiveness? This qualitative study collects data by interview, observation, and literature study. They were analyzed from the light of creative tourism. The article concludes that gastronomy tourism such as cooking class and food festival that has developed in Ubud is a form of creative tourism that help in rejuvenating the image of Ubud as cultural tourism. This happens because food and all the cooking processes as well as all the stories and values system of local wisdom attached to the local foods are part of the culture. This article contributes in providing an understanding of strengthening the image of Ubud tourist destinations as cultural tourism through creative tourism known as gastronomic tourism.